Komunikasi Partisipatoris dalam Pembentukan Desa Wisata di Desa Durian Demang Kabupaten Bengkulu Tengah (Studi Kasus di Desa Durian Demang, Kabupaten Bengkulu Tengah) - Dwi Nurina Pitasari (LONTAR: Jurnal Ilmu Komunikasi, 2019)
Durian Demang Village is a village that has natural beauty that can become a touristdestination if it is well developed. This study discusses the development communication strategy usedin the formation of a Tourism Village in Durian Deman, Bengkulu Tengah Regency so that people'seconomic lives will be better. The purpose of this study was to determine the application ofparisipatoris communication in the formation of a Tourism Village in Durian Demang Village,Bengkulu Tengah Regency. The research method used in this research is the case study method with aqualitative approach. The data collection techniques used were observation, interview,documentation study and literature study. The results of this study The participatory communicationstrategy undertaken by the Ministry of Environment and Forestry (KLHK) has an effective functionand role in providing awareness, communicating empowerment messages and developing communitycreativity in the Durian Demang Village.